(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To evaluate postoperative results of pars plana vitrectomy combined with an inverted internal limiting membrane-flap technique and intravitreal injection of viscoelastic material for optic disc pit maculopathy complicated by serous macular detachment in a child. Observations: Ocular examination included best-corrected visual acuity (BCVA) testing, slit-lamp biomicroscopy, dilated fundus examination, intraocular pressure measurement, optical coherence tomography (OCT) and color fundus photography. BCVA in the left eye was 20/50 (0.4). Preoperative OCT findings showed distortion of retinal layers, serous macular detachment and a large schisis cavity in the left eye. Foveolar depression was not determined due to the height of intraretinal fluid and subretinal fluid extending towards the optic disc pit. Retinal thickness in the macular area was 507 μm. Pars plana vitrectomy was performed in combination with an inverted internal limiting membrane internal limiting membrane-flap technique and intravitreal injection of viscoelastic material, followed by 15% C3F8 gas endotamponade. A follow-up OCT examination in 3 months showed decreased subretinal fluid, residual edema, and restored foveolar depression. Retinal thickness in the macular area was 328 μm. BCVA of the left eye improved to 20/32 (0.63). Conclusions: Pars plana vitrectomy with an inverted internal limiting membrane-flap technique for optic disc pit maculopathy allows to reduce an amount of intra- and subretinal fluid. A visco-associated flap fixation technique creates conditions for its stabilization, which ultimately contributes to improving anatomical and functional outcomes during surgery and in the postoperative period.